Pengaruh LKPD Berbasis Inkuiri Terbimbing terhadap Motivasi dan Hasil Belajar Asam Basa - Westi Sintia Berliana Prastica Br Simanjuntak; Junifa Layla Sihombing (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effect of implementing guided inquiry-based Student Worksheets (LKPD) on learning motivation and learning outcomes regarding the topic of acids and bases. This study employs a quantitative approach using a quasi-experimental method involving Grade XI students at SMA Negeri 2 Sidikalang, Dairi Regency, North Sumatra. The results indicate that the implementation of guided inquiry-based LKPD significantly increased students' learning motivation and positively influenced their learning outcomes. Furthermore, a very strong positive correlation was found between learning motivation and learning outcomes (r = 0.96; contribution of 92.1%), indicating that higher learning motivation leads to higher learning outcomes. These findings confirm that guided inquiry-based LKPD can serve as an effective alternative teaching material to enhance the quality of chemistry instruction, particularly regarding the topic of acids and bases.